Reconstructing the Concept of Zuhd in Early Islamic Generations as a Response to the Contemporary Moral Crisis - Muhammad Ihsan; Yusron Nur Hadi; Nurul Laely Mahmudah; Nasirudin Nasirudin; Abu Bakar Ahmad Baihaqy (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This article examines the reconstruction of the concept of Zuhd (asceticism) as a model of transformative social ethics in responding to the moral crisis of modern society. The rapid development of modernity, marked by globalization, technological advancement, and consumerist culture, has contributed to the rise of materialism, hedonism, and the weakening of spiritual awareness. This study aims to reinterpret Zuhd from the perspective of early Islamic generations and to contextualize its relevance in contemporary life. Employing a qualitative approach with a descriptive-analytical design through library research, data were collected from classical Sufi texts, the Qur’an, Hadith, and relevant contemporary studies, and were analysed using content analysis techniques. The findings reveal that Zuhd is not a rejection of worldly life but rather a balanced spiritual attitude that places material aspects proportionally within ethical and spiritual frameworks. The reconstruction results in four main dimensions: amaliyah (spiritual practice), Khauf (ethical awareness), moral (ethical conduct), and social critique. These dimension function integratively as a transformative ethical model capable of addressing modern moral challenges, suggesting that Zuhd can serve as a relevant ethical framework for fostering a balanced, responsible, and spiritually grounded society in the contemporary era